The effect of photoperiod on the flowering of Polytrias amaura (Buse) O. Ktze - Castro, Irma Remo 1946; Tabbada, Reynaldo A. (1977)
This paper studied the effect of photoperiod on the induction of flowering in Polytrias amaura (Buse) O. Ktza, a probable allergenic species. Plants were grown under varying lengths of light and dark period using dark chambers. The age of ripeness-to-flower, number of photo-inductive cycles needed and the effect of light-interrupted-dark-period under short-day conditions were also determined. Results showed that P. amaura is an obligate short-day plant, attaining the age of ripeness-to-flower after about 45 days and needs a minimum of 30 short-day treatments before flowering. Light-interrupted-dark-periods prevent flowering confirming further that P. amaura is a short-day plant.